A Novel Two-Step Method for Fabricating Silver Plating Cotton Fabrics. (15th September 2016) - Liu, Hao; Zhu, Lili; Xue, Jie; Hao, Lei; Li, Jin; He, Yin; Cheng, Bowen
Abstract : A novel two-step method was presented for fabricating silver plating cotton fabrics (SPCFs) with high electrical conductivity and excellent washing fastness. First, polydopamine (PDA) film was coated on the surface of cotton fabrics by in situ polymerization of dopamine, the silver ions in silver nitrate solution were reduced by the catechol groups of polydopamine, and silver nanoparticles were combined with polydopamine by covalent bond on the surface of cotton fabrics. Second, silver ions were reduced by glucose, and silver plating was coated on the surface. Subsequently, the properties of SPCFs were characterized by field emission scanning electron microscopy (FESEM), X-ray photoelectron spectroscopy (XPS) and thermogravimetric analysis (TGA), and so forth. With the increasing of silver-ammonia solution concentration or dopamine concentration, the surface resistivity of SPCFs decreases and gradually stabilized. The surface resistivity of the SPCFs can reach0.12 ± 0.02   Ω, and electromagnetic shielding effectiveness (ESE) of the SPCFs can reach58.5 ± 4.5  dB. Conductive fabrics have wide application prospect in many of fields, such as antibacterial, intelligent textiles, smart garments, electromagnetic shielding, and flexible sensors.